Ethnic inequality, the federal character principle, and the reform of Nigeria's presidential federalism - Rotimi T. Suberu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The federal character principle is Nigeria's primary formula for mitigating horizontal inequality and conflict in this chronically fractured society. Designed to guarantee inter-group inclusion in the conduct and composition of governmental institutions, the principle spans direct, integrative, and indirect policies for reducing horizontal inequalities, which overlap with consociational, centripetal, and power-dividing paradigms of ethnic conflict management. Celebrated by its champions as an ingenious approach to the management of ethnic diversity and disparity, the federal character principle has been denounced by its opponents for politicizing and valorizing sectional divisions, fostering dysfunctional and corrupt governance, and failing to effectively address structural ethnic imbalances and historical inter-group grievances. This paper offers a new narrative that transcends narrowly framed critiques of the problematic conceptualization, flawed implementation, and meagre impact of the federal character principle by underscoring the innovative design of the principle of federal character as a mechanism of ethnic consociation and integration, while highlighting the indirect variables-including profound institutional deficits in governmental accountability-that have undermined the principle's implementation and efficacy in practice.
Keywords: D63; H11; H77; N47; 330; federal character principle; horizontal inequality; North-South conflicts; ethnic diversity; integration; consociation; power-dividing